The effects of long-term experimental diabetes mellitus type I on skeletal muscle regeneration capacity - Jerković, Romana; Bosnar, Alan; Jurišić-Eržen, Dubravka; Ažman, Josip; Starčević-Klasan, Gordana; Peharec, Stanislav; Čoklo, Miran (2009)
Abstract: Muscle fibers are dynamic structures capable of altering their phenotype under various pathological conditions. The aim of the present study was to investigate the influence of long-lasting diabetes mellitus on the process of muscle regeneration in the skeletal muscle. Wistar rats were made diabetic by a single intraperitoneal injection of streptozotocin (STZ). The regeneration process in the skeletal muscle was induced in slow (m. soleus, SOL) and fast (m. extensor digitorum longus, EDL) muscles by injection of local anesthetic (bupivacaine). Skeletal muscles were analyzed 10 days, 4 and 8 weeks after bupivacaine treatment. Diabetes mellitus has changed morphological properties of both slow and fast skeletal muscles during the process of regeneration. These changes are evident in redistribution of muscle fibers and significant level of atrophy. All fiber types of diabetic fast muscles showed stronger atrophy than muscle fibers in slow muscles which have more oxidative metabolism. The changes of redistribution of muscle fibers depend on duration of diabetes and affect all types of muscle fibers
Bibliografija: 21 jed
Sažetak
Keywords: Šećerna bolest tip 1 -- Regeneracija skeletnog mišića -- Wistar štakori